2018
DOI: 10.1021/acs.analchem.7b04667
|View full text |Cite
|
Sign up to set email alerts
|

Improved Quantitative SERS Enabled by Surface Plasmon Enhanced Elastic Light Scattering

Abstract: The application of surface-enhanced Raman spectroscopy (SERS) for everyday quantitative analysis is hindered by the point-to-point variability of SERS substrates that arises due to the heterogeneous distribution of localized electromagnetic fields across a suite of plasmonic nanostructures. Herein, we adopt surface-enhanced elastic scattering as a SERS internal standard. Both elastic and inelastic (i.e., Raman) scattering are simultaneously enhanced by a given “hot spot”, and thus, the surface-enhanced elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 56 publications
1
65
1
Order By: Relevance
“…To verify if the peaks are actually enhanced or not by the presence of additional AS, we normalized the peak intensity at 965 cm À1 by that at 40 cm À1 (Figure 5a). Wei et al (2018) reported that the intensity of the surface plasmon enhanced elastic scattering signal (at 40 cm À1 in this case) scales linearly with the integrated "hot spot" signals within a laser excitation volume. Thus, intensity of other peaks can be quantified by using the peak intensity at 40 cm À1 as a normalizing factor (Wei et al 2019).…”
Section: Detection Of Sers Signal From Laboratorygenerated Nanoparticlesmentioning
confidence: 80%
See 2 more Smart Citations
“…To verify if the peaks are actually enhanced or not by the presence of additional AS, we normalized the peak intensity at 965 cm À1 by that at 40 cm À1 (Figure 5a). Wei et al (2018) reported that the intensity of the surface plasmon enhanced elastic scattering signal (at 40 cm À1 in this case) scales linearly with the integrated "hot spot" signals within a laser excitation volume. Thus, intensity of other peaks can be quantified by using the peak intensity at 40 cm À1 as a normalizing factor (Wei et al 2019).…”
Section: Detection Of Sers Signal From Laboratorygenerated Nanoparticlesmentioning
confidence: 80%
“…Figure 4 shows that all SERS spectra (from LG and AS), as well as NaCl spectra, already had peaks at 40 cm À1 and 965 cm À1 . The low frequency Raman scattering at 40 cm À1 has spontaneously emerged due to the interaction of elastically scattered light and the edge filter (Wei et al 2018). The latter peak at 965 cm À1 is more problematic in this case, since it interferes with the characteristic peak of enhanced sulfate (SO 4 2-) at $970 cm À1 , which is known to be red-shifted in SERS experiments (Gen and Chan 2017;Fu et al 2017;Tirella et al 2018).…”
Section: Detection Of Sers Signal From Laboratorygenerated Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a correction has been suggested for SERS based on normalizing against the elastic scattering. [ 70 ]…”
Section: Uncertaintymentioning
confidence: 99%
“…Spectral acquisition delivers average spectra of the diffraction-limited areas. The uniformity of the signal enhancement on a SERS substrate is most often checked by pointwise [22][23][24] or linewise 25 Raman mapping or by randomly selecting different measurement spots on the substrate 15,26,27 . However, the long spectral acquisition times hinder the imaging of large areas in high resolution in short time, for example to study the distribution of hot spots.…”
Section: Introductionmentioning
confidence: 99%